Supporting successful implementation of public health interventions: protocol for a realist synthesis. Issue 1 (December 2016) - MacDonald, Marjorie; Pauly, Bernadette; Wong, Geoff; Schick-Makaroff, Kara; van Roode, Thea; Strosher, Heather; Kothari, Anita; Valaitis, Ruta; Manson, Heather; O'Briain, Warren; Carroll, Simon; Lee, Victoria; et al.
Abstract Background There is a growing emphasis in public health on the importance of evidence-based interventions to improve population health and reduce health inequities. Equally important is the need for knowledge about how to implement these interventions successfully. Yet, a gap remains between the development of evidence-based public health interventions and their successful implementation. Conventional systematic reviews have been conducted on effective implementation in health care, but few in public health, so their relevance to public health is unclear. In most reviews, stringent inclusion criteria have excluded entire bodies of evidence that may be relevant for policy makers, program planners, and practitioners to understand implementation in the unique public health context. Realist synthesis is a theory-driven methodology that draws on diverse data from different study designs to explain how and why observed outcomes occur in different contexts and thus may be more appropriate for public health. Methods This paper presents a realist review protocol to answer the research question: Why are some public health interventions successfully implemented and others not? Based on a review of implementation theories and frameworks, we developed an initial program theory, adapted for public health from the Consolidated Framework for Implementation Research, to explain the implementation outcomes of public health interventions within particular contexts. This will guide us through the review process, which comprises eight iterative steps based on established realist review guidelines and quality standards. We aim to refine this initial theory into a 'final' realist program theory that explains important context-mechanism-outcome configurations in the successful implementation of public health interventions. Discussion Developing new public health interventions is costly and policy windows that support their implementation can be short lived. Ineffective implementation wastes scarce resources and is neither affordable nor sustainable. Public health interventions that are not implemented will not have their intended effects on improving population health and promoting health equity. This synthesis will provide evidence to support effective implementation of public health interventions taking into account the variable context of interventions. A series of knowledge translation products specific to the needs of knowledge users will be developed to provide implementation support. Systematic review registration PROSPEROCRD42015030052